Speech and language outcome measures in clinical trials of Alzheimer’s and Parkinson’s diseases - Garcia-Serrano, A (Taylor and Francis Ltd., 2026)
Introduction: Alongside core diagnostic symptoms, Alzheimer’s disease (AD) and Parkinson’s disease (PD) involve early and pervasive speech-language impairments (SLI), often appearing in preclinical stages and capturing disease severity. However, speech language outcome measures are under-represented in clinical trials, missing out on critical clinical outcome assessments (COAs). Areas covered: The purpose of this review is to survey the findings from classical (analogical) and novel (digital) speech-language measures as pathways toward more precise diagnosis and response to treatment indices in interventional clinical trials. This narrative review covers two main areas; first, it examines the strengths and limitations of SL measures in traditional cognitive testing scales to identify adequate COAs for AD and PD. Second, it overviews findings on classical and digital COAs that hold great promise despite their widespread absence in clinical trials. Expert opinion: Incorporating strategic SL COAs in clinical trials may identify early, severity-sensitive deficits and enhance the clinical insights thus obtained. The modification of clinical trial designs will nevertheless be required to increase sensitivity to identify meaningful clinical outcomes. © 2025 Informa UK Limited, trading as Taylor & Francis Group.